Changes of Glycocalyx in Steatotic Liver Graft Preservation with UW, HTK and IGL-1 Solutions. (July 2018) - Lopez, Alexandre; Panisello, Arnau; Castro-Benitez, Carlos; Rosello-Catafau, Joan; Adam, René
Abstract : Background: Static cold storage (SCS) in preservation solutions is a critical step for steatotic liver grafts submitted to ischemia-reperfusion in transplantation. Endothelial monolayer surface that covers graft endothelium named glycocalyx (GCX) protects liver endothelium against cold ischemia-injury but its alterations during cold graft preservation in UW, HTK and IGL-1 solutions have been poorly investigated. In this study, we assessed the GCX constituents such as syndecan-1 (SDC-1), heparan sulfate (HS) and glypican-1 (Gpc-1) in steatotic liver grafts after SCS in UW, HTK and IGL-1 solutions; as well as their correlation with the production of nitric oxide (NO, natural vasodilator agent) through the eNOS activation and nitrites/nitrates generation. NO contributes to prevent the exacerbated microcirculatory events in fatty liver grafts after the revascularization of the graft in liver transplantation (LT). Methods: Livers from male Zucker rats (11 weeks aged, 60% steatosis) were preserved 24h in SCS in either IGL-1 (n=5), UW (n=5) or HTK (n=5) preservation solutions and then processed for subsequent analysis. For Sham group (n=5), fatty liver specimens were directly processed after procurement. Quantification of SDC-1, Gpc-1 and HS expression were correlated with eNOS/p-eNOS relative expression and nitrites/nitrates levels. Histology and Confocal microscopy findings were also carried out. Results: GCX components (syndecan-1/heparan sulfate/GP-1) were better preserved in steatotic livers preserved 24h in IGL-1 when compared to HTK or UW. Expression of phosphorylated eNOS and Nitrite/Nitrate were higher in IGL-1 compared to HTK and UW. Conclusion: The better protection of the GCX during the SCS of steatotic livers in IGL-1 supports the better protection of endothelium with higher NO production secondary to activation of eNOS. This increase in NO production could help to improve the quality of the steatotic grafts when they are subjected to LT.